Reframing minority protection in Islamic law: Equal citizenship, human dignity, and international human rights norms - Mohamed Ahmed Zakaria Shehata (UIN Kiai Haji Achmad Siddiq Jember, 2026)
Minority protection in Muslim-majority societies remains a critical issue because it intersects classical Islamic legal thought, constitutional citizenship, and international human rights norms. Existing scholarship has examined the protective function of ahl al-dhimmah, the ethical relevance of karamah insaniyyah and maqasid al-shariah, and the relationship between Islamic law and international human rights. However, these approaches remain fragmented and have not sufficiently integrated critiques of status-based protection with dignity, equal citizenship, and the implementation gap. This article aims to reconstruct minority protection in contemporary Islamic law through the framework of dignity-based equal citizenship. It employs normative-doctrinal legal research using conceptual, philosophical, and maqasidi approaches, supported by analysis of Islamic legal concepts, human rights norms, and contemporary scholarship. The study finds that classical protection of non-Muslims contained important ethical and historical resources, but its status-based structure is inadequate for the modern constitutional state. It further shows that karamah insaniyyah, maqasid al-shariah, adaptive ijtihad, and international human rights norms can be integrated into a more substantive model of protection. The article concludes that minority protection should be reframed not as conditional tolerance, but as equal citizenship grounded in dignity, justice, public welfare, and institutional responsibility.